Tourism marketing in Bangladesh : an introduction - Hassan, Azizul (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Tourism is often a key driver of economic growth in many countries. The recent upward trends of tourism and hospitality education in higher academic institutions in Bangladesh suggests a growing tourism sector. Very little has been written on Bangladesh's tourism industry. This is the first edited volume published from an international publisher which looks at this industry and how it has developed and flourished. The book begins by looking at tourism policy planning and provides a comprehensive overview of topics from tourism products and services in Bangladesh to how they are being marketed. It also discusses how private and public tourism institutions can address future long term trends. This book will appeal to those interested to learn more about developing tourism industry in emerging economies and may provide invaluable lessons from Bangladesh's experience and success.
Part 10 Tourism marketing and country image -- 17 The curious case of Bangladesh and Nepal: tourism advertising to transform country image and empower developing countries -- Part 11 Future trends, implications and challenges -- 18 Potentials of tourism products and services in Bangladesh -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Bangladesh -- Marketing; Tourism -- Bangladesh; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism